Tracking collector consideration of tilted collector solar updraft tower power plant under Malaysia climate conditions - Gitan, A.A. (Elsevier Ltd, 2015)
SUPP (Solar Updraft Tower power plant) is a technology in the power generation sector. The power productivity and efficiency represent important performance characteristics of SUPP. In the present work a mathematical model was developed to estimate the performance of SUPP based on tracking solar collector consideration in Malaysia. The objective is to verify the suggested model and to optimize the slope angle of tilted tracking solar collector. Basically, the hourly solar data were analysed considering solar azimuth angle for tracking case calculation to determine the solar energy incident on the collector. Then, the useful energy gain was calculated based on heat transfer relations. The model was validated with experimental work and well agreement was achieved. Results revealed that the SUPP of slope collector angle of 10Â° can produce higher power generation over the whole the year. Also, the tracking solar consideration enhanced the performance characteristics especially the power productivity by around 3.5 kW over that of fixed collector. The maximum collector and SUPP efficiencies of 51 and 0.165 respectively were obtained. Â© 2015 Elsevier Ltd.